Operational Optimization in Chilean SMEs through Information and Communication Technologies - Florencia Flen Rossi; Jorge Rojas-Vallejos; Mario Domínguez Amorós (Ensayos Revista de Economía)
Objective: This study analyzes the impact of Information and Communication Technologies (ICT) on the operational efficiency of Chilean Small and Medium Enterprises (SMEs), aiming to identify the most relevant digital tools to support their development and guide public policy.